ANALYSIS OF THE LAWS OF GROWTH AND DEVELOPMENT OF PRIMARY CLASS STUDENTS (Scientific journal of the Fergana State University, 2024)
This article analyzes the laws of growth and development of elementary school students, and it is envisaged that the activity of organs and systems will improve during the child's growth and development. Also, based on the children's anthropometric indicators, we evaluated the development of all vital organ systems and body growth according to their age.